Inflation and counter-inflationary policy measures: The case of Croatia - Bernd Christoph Ströhm (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
This national case study will investigate recent inflationary developments in Croatia by combining quantitative analysis with a qualitative overview of policy making. It collects data regarding inflationary developments, wages and other key variables in Croatia's economy. The task of this study is to lay out wage and price developments within the country and to demonstrate structural aspects of inflation in light of post-covid recovery, supply-chain disruptions, and Russia's military invasion of Ukraine, causing surging inflation rates across Europe. To demonstrate the development of nominal wages, prices and corporate mark-ups, this study will utilise data by Eurostat and the Croatian Bureau of Statistics. In addition to researching inflationary developments, this study shall also analyse policy making and the evolution of policies by the government, aimed at tackling inflationary pressure in Croatia, including measures to support businesses and local households in managing surging energy costs. Croatia's energy dependency and its role as potential energy hub for the Western Balkan region shall be illustrated as well. Furthermore, this study describes the structure of Croatia's labour market and reflects wage negotiations between trade unions and the government.
urn:nbn:de:101:1-2023011911271267682770
Keywords: 330; AK Wien; Croatia; Inflation; gas; electricity; price cap; HICP; energy; distribution; social pact; real wages